Effect of Thickness on Conductivity of (ZnO:AlCl2) TCO Thin Film - dian mart shoodiqin; fadli robiandi; fifin tresna juwita; virgi al yulia manarisip (JST (Jurnal Sains Terapan), 2021)
Massive materials engineering has been carried out to get a certain function of a material. One of the intensively carried out researches in the development of conductive glass as the base material for solar cells. based on these facts, this research was conducted to develop a functional material. (ZnO:AlCl2) TCO thin film has been deposited on a glass substrate using DC sputtering technique. The objective of this research is to study the effect of time deposition, the distance of substrate, morphology of surface, and microstructure (ZnO: AlCl2) thin film, so that it can be used as a component in the solar cell. The characterization has been performed with Scanning Electron Microscopy to investigate the surface morphology and the electrical resistivity was done by doing the four-point probe method. The result showed that long deposition causes the layers on the substrate to overheat so that the Zn deposition in the layer is oxidized. The thickness of the layers increases followed by the resistivity of the deposition layers.Keyword: Thickness, Conductivity, Thin Film.